Potensi Herpetofauna Dalam Pengobatan Tradisional Di Sumatera Barat - Rivi Hamdani; Djong Hon Tjong; Henny Herwina (Universitas Andalas, 2013)
The research about potential of herpetofauna on traditional medicine in West Sumatera was conducted from March to August 2012. This research was conducted at several districts in West Sumatera such as Batusangkar, Padang, Payakumbuh, Pasaman, Painan and Sijunjung. The survey and quisioner method were used by interviewing informan about the species of herpetofauna which were used in traditional medicine. A total of 5 reptilian species were recognized as medicine such as Eutropis multifasciata (Bingkaruang), Naja sumatrana (Ula sendok), Phyton reticulatus (Piton), Chelonia mydas (Katuang), Dogania subplana (Labi-labi) and one species of amphibian i.e Hylarana erythrea (Koncek hijau) from Ranidae.Keywords: potential, herpetofauna, tradicional medicine, West Sumatera